Memorising Traditions and Challenges in Guidance Counselling - Ilyas, Muhammad; Wijaya, Firad (Contemporary Society and Politics Journal, 2024)
Learning guidance with memorization methods is an important form of guidance service that should be provided in educational institutions. Memorization means the activity of intentionally and earnestly remembering. Learning guidance through memorization focuses more on identifying difficulties in memorizing lesson material, which includes problems with recognition difficulty, recalling, and the ability to use old memories to recognize new ones. The research method used is descriptive qualitative research in the form of library research, which utilizes books and other literature related to the research theme. Based on the issues of difficulties in memorizing lesson material among students, this shows that if these problems are not immediately addressed, they will significantly affect the students’ learning achievement. Therefore, solutions to the problems related to difficulties in memorizing lesson material among students should be found to avoid poor academic performance. This aligns with the duties and roles of counselors in providing learning guidance and counseling through memorization methods.